DIRECT PCR-RFLP BASED SPECIES IDENTIFICATION OF INDIAN WILD CARNIVORES BY NON-INVASIVE SAMPLING (Applied Biological Research, 2023)
In field conditions such as forest ranges, movement corridors or in areas prone  to man animal conflict very often the only evidence/specimens available for  investigation are animal scat, fur, hairs, epidermis, etc. Since animal scat  contains denuded intestinal epithelial cells it can provide genetic material which  can be used for further analysis and other downstream studies. In present study  surface scrapings from faecal samples of 5 different carnivore species viz., tiger  (Panthera tigris), lion (P. leo), leopard (P. pardus), domestic dog (Canis familiaris)  and domestic cat (Felis catus) were collected for DNA extraction using standard  kit based protocols. A fragment of 16S rRNA gene of mitochondrial DNA was  amplified using specific primers. The amplicons generated were subjected to  restriction digestion. Species identification and differentiation was done using  fragment length polymorphism (PCR-RFLP). The results depicted the utility  and effectiveness of molecular scatology based PCR-RFLP technique for  identification of wild carnivore species in forensic investigations. The  observations also highlighted the potential of highly conserved mitochondrial  DNA markers like 16SrRNA gene to be employed for species identification and  differentiation of wild carnivores.
Keywords: Carnivores; forensic; markers; mtDNA; PCR-RFLP; scatology; speciation; sympatric